Influence of Perceived Ease of Use and Perceived Usefulness towards Continuance Intention with Customer Satisfaction as Intervening Variable: a study of Startup Companies Using e-Wallet - Novira, Delvi; Utomo, Humam Santosa; Mulyanto, Indro Herry (Journal of Business Management and Economic Development, 2024)
The use of e-wallets is increasingly needed by entrepreneurs to improve their business performance. This study aims to examine and analyze the effect of perceived ease of use on perceived usefulness, customer satisfaction, and continuance intention. This research was conducted on students who own businesses and use e-wallets to operate their businesses. The sampling technique used was purposive sampling. Respondents used in this study amounted to 85 people. Data analysis using SEM-PLS. The results of the study found that Perceived Ease of Use has a significant effect on Customer Satisfaction, Perceived Ease of Use has no significant effect on Continuance Intention, Perceived Usefulness has a significant effect on Customer Satisfaction, Perceived Usefulness has no significant effect on Continuance Intention, and Customer Satisfaction has a significant effect on Continuance Intention. The results of this study suggest that e-wallet companies increase customer satisfaction because they play an important role in linking Perceived Ease of Use and Perceived Usefulness to Continuance Intention.